B‐flow ultrasound facilitates visualization of contrast medium during hysterosalpingo‐contrast sonography. (9th July 2014) - Sladkevicius, P.; Zannoni, L.; Valentin, L.
ABSTRACT Objective To assess if B‐flow ultrasound improves visualization of flow of contrast medium in the Fallopian tubes during hysterosalpingo‐contrast sonography (HyCoSy) compared with grayscale ultrasound. Methods This prospective observational study included 160 women referred for HyCoSy as part of infertility work‐up between January 2011 and September 2012. In each woman, at the same session, HyCoSy was performed first using saline with air and then using Sonovue®, and for each contrast medium, grayscale ultrasound was first used and then B‐flow ultrasound was used. Flow of contrast was observed in three parts of each tube: intramural, middle and distal. Results In 129 (81%) women, flow of Sonovue was observed in the intramural part of both tubes and in the pouch of Douglas when using grayscale ultrasound. In these women, flow of Sonovue was seen in the middle part of 70% of the 258 tubes when using grayscale ultrasound and in 93% when using B‐flow ultrasound; and in the distal part in 81% when using grayscale ultrasound and in 98% when using B‐flow ultrasound. When using air and saline, flow was seen in the intramural part of 90% and 93% of the tubes, in the middle part in 54% and 72%, and in the distal part in 66% and 90%, using grayscale ultrasound and B‐flow ultrasound, respectively. Conclusion B‐flow ultrasound facilitates detection of flow of contrast in the middle and distal parts of the tubes at HyCoSy, especially when a mixture of saline and air is used as contrast medium. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd